Bahasa Sasak Alus Dan Bahasa Indonesia: Familiarisasi Bahasa Pinjaman Dalam Menumbuhkan Karakter Kesantunan Anak Usia Dini - Nahdi, Khirjan; Wathoni, Hamzani; Ilhami, Baiq Shofa (Jurnal Golden Age, 2020)
This article examines the process of familiarization the Sasak Alus Language into Indonesian language communication in early childhood. Through descriptive methods in the sociopragmatic study, this study aims to find forms of communication politeness character and the process of forming the character of early childhood politeness through loan languages. This study is strategic in two ways; first, the process of forming dominant characters is a deliberate and conscious activity through the learning system.Â  This study shows the natural process and non-indoctrination. Second, sociopragmatic studies always place the process of language lending as a disruption of language events in a multilingual context. This study shows a positive contribution to the growth of politeness in language from an early age. Previously with word class grouping techniques and the description of communication context, it was found that familiarization of the loan language of the Sasak Alus language into Indonesian communication fostered the character of politeness in communicating early childhood. Previously with word class grouping techniques and the description of the communication context, it was found that familiarization of the loan language of the Sasak Alus language into Indonesian communication fostered the character of politeness in communicating early childhood. This character is obtained through the use of the loan word Sasak Alus in Indonesian communication. The word loan consists of five classes of words, namely pronouns, interrogative, adverb modality (event), adverb quantity (tense), and demonstrative. The five classes of words are said in a flat, hoarse tone, until decrease. The pronunciation of words in that tone contains four motivations, namely to humble yourself, respect the other person, position yourself as part of others, and continue communication. The process is carried out early on through the process of inculcation of character by adults through the exemplary process.